2002
DOI: 10.1055/s-2002-20529
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-Thyroid Axis, Thyroid Volume and Leptin in Healthy Adults

Abstract: We did not find any correlation between leptin levels and pituitary-thyroid axis in this control population. The correlation between leptin and thyroid volume in females is probably a consequence that leptin and thyroid volume are regulated in parallel by variables relating to anthropometry and body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
3
22
1
1
Order By: Relevance
“…Oberhofer et al reported the mean thyroid volume as 13.35 ml (man 14.94 m, women 12.09 ml in 500 healthy adults at 1989in Austria (15). Gomez et al reported the thyroid volume as 9.8±4.6 ml form an and 6.5±2 ml for women (16). In our study these volumes were 15.87±7.18 ml and 10.94±4.53 ml respectively (mean 13±6 ml) (p=0.000).…”
Section: Discussionsupporting
confidence: 49%
“…Oberhofer et al reported the mean thyroid volume as 13.35 ml (man 14.94 m, women 12.09 ml in 500 healthy adults at 1989in Austria (15). Gomez et al reported the thyroid volume as 9.8±4.6 ml form an and 6.5±2 ml for women (16). In our study these volumes were 15.87±7.18 ml and 10.94±4.53 ml respectively (mean 13±6 ml) (p=0.000).…”
Section: Discussionsupporting
confidence: 49%
“…25 However, it must be emphasized that this putative relation between TSH and leptin is not supported by all studies. 26,27 We only found the relation between TSH and BMI in nonsmokers. A similar but weaker trend was seen in the smokers, but the results were not statistically significant.…”
mentioning
confidence: 83%
“…Thyroid volumetry was performed according to the method of Brunn et al (11) and as previously described (12) . To assess thyroid enlargement, two different reference values for Tvol were used: an old reference value where thyroid enlargement was defined as a Tvol exceeding 18 ml (13) and a revised reference value where we defined thyroid enlargement as a Tvol exceeding 12?5 ml (14,15) . The revised reference value is based on a healthy, non-iodine deficient Spanish population and mean Tvol (6?5 ml) 1 3SD (6?0 ml) in this population was used to define the cut-off of 12?5 ml (14,15) .…”
Section: Methodsmentioning
confidence: 99%